Analyses of Medical Malpractice in Judicial Appraisal: 505 Cases - Meng You; Xu Wang; Di Lu; Haidong Zhang; Shengli Di; Fengqin Zhang; Zhaoming Guo; Li Yuan; Lin Chang; Jian Xiang; Lili Yu; Yingkai Yang; et al. (Wolters Kluwer Medknow Publications, 2015)
The purpose of this paper is to investigate and analyze the current situation of medical malpractice and make suggestions for preventative measures from a judicial appraisal standpoint. From 2002 to 2011, we conducted and analyzed 505 medicolegal malpractice experiments at the Fada Institute of Forensic Medicine and Science (FIFMS) in Beijing, People's Republic of China (PRC). We found that the occurrence of medical disputes in surgical and obstetrical/gynecological cases seemed more frequent. The main causes of medical disputes included issues regarding medical ethics, poor quality of the medical staff, equipment malfunctions, and dereliction of duty by the medical personnel. The reasons for dissatisfaction varied among the different levels of medical service. Basic medical services garnered the most complaints. If we can work to improve the moral and professional standards of the medical staff members, intensify their ethics, and foster good relationships between patients and medical professionals, the quality of medical care would improve and the number of disputes regarding medical services would be reduced.